2017
DOI: 10.15252/embj.201695602
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence properties that predict susceptibility to epiallelic switching

Abstract: Transgenerationally heritable epialleles are defined by the stable propagation of alternative transcriptional states through mitotic and meiotic cell cycles. Given that the propagation of DNA methylation at CpG sites, mediated in Arabidopsis by MET1, plays a central role in epigenetic inheritance, we examined genomewide DNA methylation in partial and complete loss‐of‐function met1 mutants. We interpreted the data in relation to transgenerational epiallelic stability, which allowed us to classify chromosomal ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 35 publications
6
72
0
Order By: Relevance
“…All six lines selected from top performing F 2 plants showed a reduction of enhanced growth by F 2:6 , further confirming the epigenetic nature of MSH1-derived growth changes, with similar dissipation patterns described previously in Arabidopsis ddm1 epiRILs (Cortijo et al, 2014;Roux et al, 2011). A recent study has suggested that stability and switching of acquired epigenetic states are influenced by DNA sequence composition and repetitiveness (Catoni et al, 2017). It is also speculated that methylation variation not linked to a causal genetic variant tends to be less stable than when directly linked to genetic change (Schmitz et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…All six lines selected from top performing F 2 plants showed a reduction of enhanced growth by F 2:6 , further confirming the epigenetic nature of MSH1-derived growth changes, with similar dissipation patterns described previously in Arabidopsis ddm1 epiRILs (Cortijo et al, 2014;Roux et al, 2011). A recent study has suggested that stability and switching of acquired epigenetic states are influenced by DNA sequence composition and repetitiveness (Catoni et al, 2017). It is also speculated that methylation variation not linked to a causal genetic variant tends to be less stable than when directly linked to genetic change (Schmitz et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…They found that proximal methylation levels are most predictive. In a slightly different setting, Catoni et al (2017) identified features in transposable element-like sequence, including high repeat content and low CG density, that predict the efficient re-establishment of CG methylation loss in lines following transient disruption of an enzyme responsible for maintenance of CG methylation. Following in these footsteps, comprehensive deep learning approaches are underway to identify chromatin and sequence features that determine the 'epimutability' of specific loci in plant genomes.…”
Section: Predicting the 'Epimutability' Of Specific Locimentioning
confidence: 99%
“…Converted samples were immediately used to prepare bisulfite libraries employing the TrueSeq DNA 259 We computed chloroplast mappability on the eggplant genome using the gem-mappability tool from the Gem 275 library (Derrien et al, 2012), with a k-mer size of 75 bp and allowing a maximum of one mismatch, and only 276 unique regions (mappability = 1) were used to estimate conversion. To account for non-converted DNA, we 277 applied a correction according to Catoni et al (2017). Briefly, the number of methylated reads were decreased 278 as: m*= max(0, mnc) (where m* is the corrected number of methylated reads, m is the raw number of 279 methylated reads, n is the total number of reads and c is the conversion rate).…”
Section: Library Preparation and Sequencing 258mentioning
confidence: 99%